Strategi Efisiensi Produksi dan Rantai Pasok Gula Aren Melalui Integrasi Lean Manufacturing dan Manajemen Risiko untuk Ketahanan Pangan Sumbawa Barat - Gita Adita Risma; Nispi Azzumardi; Ananda Syalsabila Hidayat; Junaidi Efendi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Palm sugar is a local food commodity with the potential to support food security and boost the local economy in West Sumbawa Regency. However, the production process and supply chain still face various challenges, such as waste, low efficiency, inconsistent product quality, and risks that affect the smooth flow of production and distribution. This study aims to analyze waste using the Lean Manufacturing approach, analyze supply chain risks through risk management, and formulate a strategy to integrate these two approaches to improve production efficiency. The study employs a descriptive method with a case study approach through observation, interviews, documentation, and literature review. Analysis was conducted using Value Stream Mapping, identification of the Seven Wastes, Fishbone Diagrams, and a Risk Matrix. The results show that value-added activities account for only 28.11%, while non-value-added activities account for 71.89%, with “waiting” being the dominant form of waste. The integration of Lean Manufacturing and risk management yields improvement strategies capable of reducing waste, lowering risk, increasing production efficiency, strengthening the supply chain, and supporting local food security.